Coal deposits of Turkey: properties and importance on energy demand - Oskay, R. G.; Inaner, H.; Karayigit, A. I.; Christanis, K. (Bulletin of the Geological Society of Greece, 2013)
In the last two decades electricity generation and consumption in Turkey was increasing steadily. Around 80% of the electricity generated is derived from fossil fuels such as imported natural gas and oil, and domestic coal. As the energy policy now is focusing on reducing the dependency on imported fuels, coal, particularly this of low-rank, is becoming important for the country. Latest explorations showed that total coal reserves of Turkey reach to 13 Gt with low-rank coals (i.e. lignite and sub-bituminous) being dominant. Coal deposits, formed under various conditions and in various geological times, are widely spread over the territory. The most significant deposits are of Tertiary, especially Neogene age. Neogene coals are most appropriate for combustion in the thermal power plants due to the high total reserves despite the high ash yields and the low calorific values. We imply that applying reasonable exploitation planning and appropriate washing techniques, coal will play a key role in future energy supply of the country.